DESIGNING ARCHITECTURE TECHNOLOGY BASED CLOUD COMPUTING IN BUILDING MATERIALS MANUFACTURER - Fajar Muttaqi (Universitas Utpadaka Swastika, 2023)
Users can access the necessary services from anywhere and at any time thanks to the cloud computing technology, which places the majority of processing and computing on the Internet. However, in practice, each business develops its own information systems architecture and requirements. This brings up a number of issues, including the potential for redundant information systems, the lack of data structure standards, the inability of information systems to consolidate their data, and inconsistent information system development. The motivation behind developing a model of information technology architecture using the idea of cloud computing stems from some of these issues. A cloud-based information technology architectural model was created in line with the requirements and needs of the organization based on the analysis of the company's state and the use of the chosen framework. Another Indonesian company is anticipated to benefit from the research, primarily as a resource for constructing the information technology architecture.